UNDERSTANDING SUSTAINABLE ENTREPRENEURSHIP STUDY THROUGH BIBLIOMETRIC ANALYSIS (GROUNDED THEORY) - Nuringsih, Kartika; N, Nuryasman M.; Maupa, Haris; Payangan, Otto R. (Graduate Program of Universitas Tarumanagara, 2023)
To harmonize sustainable development in the entrepreneurship sector, a study was carried out to get an overview of knowledge mapping and current issues on sustainable entrepreneurship. Qualitative research was conducted through bibliometric analysis using VosViewer on Scopus metadata for exploring a grounded theory. The density of visualization shows that the yellow color gradation on sustainable entrepreneurship is opaquer than the entrepreneurship’s color, so it is new to be developed as a novelty. The visualization overlay captures the linked topics of entrepreneurial studies since 2008. It is looked at some issues e.g., innovation, sustainability and development which are the gradating color of light green that has been published since 2014-2015. Conversely, other topics e.g., sustainable business models, social capital performance, business venture, and social entrepreneur are detected as current issues. On sustainable entrepreneurship, the overlay of visualization depicts the linked among specific topics e.g., entrepreneurial intention, higher education, business model, and SMEs which has been published since 2012. The further study will improve the topic of sustainable entrepreneurial intention by involving the social domain as a novelty. The bibliometric analysis results in science mapping as the basis for building a state of the art so that researchers can elaborate on ontology issues, and build epistemology and axiology in this study.